2013
DOI: 10.1021/es403368j
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Verification of TiO2 Accumulation in Cucumber Fruit: A Possible Pathway of TiO2 Nanoparticle Transfer from Soil into the Food Chain

Abstract: The transfer of nanoparticles (NPs) into the food chain through edible plants is of great concern. Cucumis sativus L. is a freshly consumed garden vegetable that could be in contact with NPs through biosolids and direct agrichemical application. In this research, cucumber plants were cultivated for 150 days in sandy loam soil treated with 0 to 750 mg TiO2 NPs kg(-1). Fruits were analyzed using synchrotron μ-XRF and μ-XANES, ICP-OES, and biochemical assays. Results showed that catalase in leaves increased (U mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
176
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(199 citation statements)
references
References 37 publications
19
176
3
1
Order By: Relevance
“…TiO 2 NPs have also been reported to be toxic to plants. Servin et al (2013) reported that TiO 2 NPs induced macromolecular changes in cucumber fruit. In addition, there is evidence that TiO 2 in the nano-anatase form increases antioxidant stress in spinach chloroplasts (Zheng et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 NPs have also been reported to be toxic to plants. Servin et al (2013) reported that TiO 2 NPs induced macromolecular changes in cucumber fruit. In addition, there is evidence that TiO 2 in the nano-anatase form increases antioxidant stress in spinach chloroplasts (Zheng et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The selected plants were hydroponically grown in modified Hoagland nutrient solution for 7 d in an environmental growth chamber (Environmental Growth Chamber, Chagrin Falls, OH) with a 14-h photoperiod, illumination of 340 µmol/(m 2 ·s), 25 °C/ 20 °C day/night temperature, and 65% relative humidity. Cultivation was performed as previously described by Servin et al (2013).…”
Section: Plant Growth and Tio 2 Np Treatmentmentioning
confidence: 99%
“…Typically, nanoparticles will accumulate in certain tissues and organs, in the same way it happens with animals (Varna et al, 2012). As commented above, plant organs acting as strong sinks for sap and nutrients are likely to accumulate nanomaterials traveling through the vascular system, mainly fruits (Servin et al, 2013), grains (Lin et al, 2009), flowers, and young leaves (Cifuentes et al, 2010;Koo et al, 2015). That is something to be used in our advantage when deciding the role of the nanomaterial we want to test.…”
Section: Movement Of Nanoparticles Inside Plantsmentioning
confidence: 99%
“…Malondialdehyde content serves as an indicator of the extent of lipid peroxidation and an indirect reflection of the extent of cell damage (Wang et al, 2011). Servin et al (2013) reported an increase in CAT activity (250-750 mg/kg) but a decrease in APX (500 mg/kg) when cucumber plants were exposed to nano TiO 2 . Also, Laware and Raskar (2014) reported that CAT and GPX activities can be enhanced in the presence of 10-30 μgml -1…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is reported that metal oxide nanoparticles exposure can induce the generation of ROS, consequently causing oxidative stress and activating plant responses for detoxification such as enzymatic activity (Ma et al, 2015). Similarly, Servin et al (2013), Hong et al (2005) and Song et al (2013) reported an increase in the activities of SOD, CAT, POD and decreased accumulation of ROS when plants were exposed to TiO 2 nanoparticle.…”
Section: Introductionmentioning
confidence: 96%